On fluctuations of the Black Sea basin after the Last Glacial Maximum and Early Holocene - Slavova, K. (Геология и полезные ископаемые Мирового океана, 2009)
The aim of this paper is to determine the causality between the cycles of Solar Luminosity on the one hand, and the palaeoclimatic data for the Black Sea region and the fluctuations of the Black Sea Basin on the other hand. The established cycles of Solar Luminosity can explain the short periodicity fluctuation of the Black Sea level. It is considered, that the regression of the Black Sea Basin to the depth of –90…–100 m below the contemporary sea level during the Early Holocene is not abrupt event.